Depressive and Anxious Temperaments as Predictors of Late Onset Bipolar Disorder? Preliminary Results of a “Real World” Exploratory Study - Orsolini, Laura; Menculini, Giulia; Tempia Valenta, Silvia; Fiorani, Michele; Rocchetti, David; Salvi, Virginio; Tortorella, Alfonso; Volpe, Umberto (Frontiers in Psychiatry, 2022)
Introduction Bipolar disorder (BD) onset typically occurs between 15 and 30 years, being diagnosed under the age of 50 in 90% of cases, named “non-late onset BD” (non-LOBD). However, clinical observation of late-onset BD (LOBD) raised some concern regarding a differential psychopathological pattern, outcomes and treatment, including a specific affective temperament vulnerability. Therefore, an exploratory study in the “real world” was carried out by investigating psychopathological and temperamental features of a psychogeriatric cohort of LOBD and non-LOBD subjects. Methods A total of 180 patients affected with BD-I, BD-II, and Cyclothymic Disorder were screened in a Mood Disorder Outpatient Service, during the timeframe January 2019-August 2021. Out of 78 enrolled outpatients, 66 (33 non-LOBD, 33 LOBD) were recruited, by the retrospective collection of sociodemographic, cognitive, psychopathological and clinical assessment, including the short-version of the Temperament Evaluation of Memphis, Pisa, and San Diego (TEMPS-M). Results LOBD is significantly associated with higher rates of BD-II diagnosis (χ2 = 27.692, p < 0.001), depressive episodes (p = 0.025), mixed states (p = 0.009), predominant depressive and anxious affective temperaments (p < 0.001). Non-LOBD is significantly associated with higher endocrinological (χ2 = 6.988, p = 0.008) and metabolic comorbidity (χ2 = 5.987, p = 0.014), a diagnosis of BD-I, manic episodes, and predominant hyperthymic affective temperaments (p = 0.001). GDS (p < 0.001) and MSRS (p = 0.005) scores were significantly higher in LOBD. Conclusion Further longitudinal studies with larger sample sizes and a control group are needed to determine whether LOBD may represent a distinct psychopathological entity from non-LOBD and evaluate differences (if any) in terms of prognosis and treatment between non-LOBD and LOBD.